Trends in Childhood Thyroid Cancer incidence in Korea and Its Potential Risk Factors - Park, Jun; Park, Hyunju; Kim, Tae Hyuk; Kim, Sun Wook; Jang, Hye Won; Chung, Jae Hoon (Frontiers in Endocrinology, 2021)
Background: The incidence of thyroid cancer has increased, but it has decreased recently due to the decrease in screening tests in Korea. Childhood thyroid cancer has been an increase in the past as the same trend as adults, but there have been few reports on recent trends. We analyzed the trends of thyroid cancer in Korean children and related factors. Methods: From national statistics and cancer register database, the data of age-specific incidence rate in Korean childhood thyroid cancer from 1999 to 2017 was obtained, and levels of seaweed intake, the number of computed tomography (CT) and neck ultrasonography (US), obesity prevalence rate, and smoking and alcohol consumption rates in children were analyzed. Results: The age-specific incidence of thyroid cancer in Korean children has increased in both genders between 1999 and 2017 (2.0 in 1999 vs. 7.2 in 2017, per population of 100,000), especially in the age group of 15-19 years (1.5 in 1999 vs. 5.5 in 2017, per population of 100,000). During the same period, levels of seaweed intake, number of CT scans and neck US, and prevalence of obesity in children increased significantly, while childhood smoking and alcohol consumption rates decreased. Conclusion: Unlike the adult thyroid cancer in Korea, childhood thyroid cancer continues to increase, and the cause might be accompanied by actual increases due to the environmental factors such as excessive iodine intake, exposure to medical radiation, and increased obesity prevalence as well as the screening effect.